A network analysis of China’s Central Committee: a dynamical theory of policy networks - Sibayan, Jerome Tan (Kansas State University, 2013)
How does the social network structure of China’s Central Committee influence the direction and timing of intra-Party events, domestic policies, and foreign policies? How do changes in network structures explain specific patterns and propensities for policy change? The purpose of this study is to describe the social network structure of the Chinese Communist Party’s Central Committee from 1922 to 2011 and to explore the relationship between changes in the network and policy trends. This study draws on policy network theory, network dynamics, Veto Player Theory and Prospect Theory which together posit that dynamic network structural characteristics influence policy outcomes. I introduce a dynamical theory of policy networks and describe some observable implications. This mixed method analysis is based on a new network dataset and follows two major lines of investigation. A structured, focused comparison of case studies associates changes in the Central Committee’s network structure in 1969, 1978, 1982, and 1997 with consequent policy outcomes and demonstrates the explanatory power of the dynamical theory. Statistical analyses of China’s foreign policies (1949-1978 and 1984-1995) and China’s domestic policies (1984-1995) suggest the dynamical theory is generalizable. Changes in paramount leader and potential competitor centralities and Central Committee centralization are important causal factors explaining the timing and type of intra-Party, domestic, and foreign policies.
Keywords: Social network analysis; China's Central Committee; Policy networks; Guanxi; Political Science (0615)